Clinical, laboratory and molecular findings and long-term follow-up data in 96 French patients with PMM2-CDG (phosphomannomutase 2-congenital disorder of glycosylation) and review of the literature. Issue 12 (27th September 2017) - Schiff, Manuel; Roda, Céline; Monin, Marie-Lorraine; Arion, Alina; Barth, Magali; Bednarek, Nathalie; Bidet, Maud; Bloch, Catherine; Boddaert, Nathalie; Borgel, Delphine; Brassier, Anaïs; Brice, Alexis; et al.
Abstract : Background: Phosphomannomutase 2-congenital disorder of glycosylation (PMM2-CDG) is a multisystem inborn error of metabolism. Objectives: To better characterise the natural history of PMM2-CDG. Methods: Medical charts of 96 patients with PMM2-CDG (86 families, 41 males, 55 females) were retrospectively reviewed. Data on clinical, laboratory and molecular parameters at diagnosis were analysed. Follow-up data at last examination were reported for 25 patients. Results: The patients were born between 1963 and 2011. Diagnosis of PMM2-CDG was made at a mean (SD) age of 6.8 (8.5) years. The presenting signs were mostly neurological (hypotonia, intellectual disability, cerebellar syndrome) and observed in almost all the patients. A total of 38 patients (14 males, 24 females) exhibited, in addition to neurological signs, visceral features including at least one of these: feeding difficulty requiring a nutritional support (n=23), cardiac features (n=20; pericarditis: 14, cardiac malformation: 9, cardiomyopathy: 2), hepato-gastrointestinal features (n=12; chronic diarrhoea: 7, protein-losing enteropathy: 1, ascites: 3, liver failure: 1, portal hypertension: 1), kidney features (n=4; nephrotic syndrome: 2, tubulopathy: 2) and hydrops fetalis (n=1). Twelve patients died at a mean age of 3.8 years (especially from pericarditis and other cardiac issues). Laboratory abnormalities mostly included elevated transaminases and abnormal coagulation parameters. High thyreostimulin levels, hypocholesterolemia, hypoalbuminemia and elevated transaminases were associated with the visceral phenotype. Besides the common Arg141His PMM2 variant harboured by half of the patients, 45 different variants were observed. Conclusions: PMM2-CDG clinical phenotype is heterogeneous in terms of clinical course, with no clear division between neurological and visceral presentations.